PRN Medication Events in a Forensic Psychiatric Hospital: A Document Analysis of the Prevalence and Reasons - Hipp Kirsi; Repo-Tiihonen Eila; Kuosmanen Lauri; Katajisto Jouko; Kangasniemi Mari (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
The aim of this study was to describe and explain the prevalence and reasons for as needed medication (pro re nata, PRN) in a forensic psychiatric hospital. We reviewed the documents of 67 long-term inpatients (87% male) over the one-year study period and identified 8626 PRN events. Virtually all of the patients received PRN for physical reasons, just over half for psychiatric reasons, and just over one-third for insomnia. The number of PRN events per patient was unevenly distributed. The prevalence of PRN events for both psychiatric reasons (26%) and insomnia (14%) were associated with the female gender, more severe psychiatric symptoms, and lower daily functioning. Half of the patients did not receive PRN for psychiatric reasons. It is likely that the use of such medication was successfully mitigated with scheduled medication and psychosocial approaches. The high number of PRN events for physical reasons (60%) was not explained by the patient characteristics and urgent research is needed on this aspect. Protracted PRN use should be recognized in clinical practice, and consider more structured solutions to develop PRN protocols and evidence-based care. Future research should examine how PRN is integrated with patients' regular treatment and non-pharmacological methods.